Return on Assets Loss from Situational and Contingency Misfits - Burton, Richard M.; Lauridsen, Jørgen; Obel, Børge (Management Science, 2002)
We develop a rule-based contingency misfit model and related hypotheses to test empirically the Burton and Obel (1998) multi contingency model for strategic organizational design. The model is a set of “if-then” misfit rules, in which misfits lead to a loss in performance; they are complements to the strategy and organizational contingency theory fit rules. Using data from 224 small- and medium-sized Danish firms, misfits are categorized and identified. Then, performance hypotheses are developed and tested using regression models. We confirm the hypotheses that firms with situational misfits or contingency misfits, or both, incur performance losses in return on assets compared with firms with no misfits. Contrary to our hypotheses, we did not find that additional misfits lead to increased performance loss. Our results suggest that just one misfit of any kind may significantly compromise performance. These results yield a deeper understanding of organizational contingency theory, as well as implications for the rule-based fit-misfit organizational design model.